Clinical Magnetic Resonance Imaging of the Knee at 7 T: Optimization of Fat Suppression. Issue 3 (March 2019) - Wyss, Michael; Manoliu, Andrei; Marcon, Magda; Spinner, Georg; Luechinger, Roger; Pruessmann, Klaas P.; Andreisek, Gustav
Abstract : Purpose: The aim of this study was to evaluate the efficiency and performance of different fat suppression techniques for clinical 7 T knee magnetic resonance imaging including the slice-selective gradient reversal (SSGR) technique. Materials and Methods: This article is an ethical board–approved prospective study with written informed consent from 8 volunteers (mean, 31 ± 4 years). It included fat phantom and knee magnetic resonance imaging at 3 T (Magnetom Skyra; Siemens Healthcare) and at 7 T (Achieva, Philips Healthcare). At 3 T, an axial proton density-weighted turbo spin echo sequence with spectral adiabatic inversion recovery (SPAIR) was acquired. At 7 T, a series of 5 proton density-weighted turbo spin echo sequences was acquired: ( a ) without fat suppression, ( b ) with spectral presaturation with inversion recovery (SPIR), ( c ) with SPAIR, ( d ) with SSGR, and ( e ) with the combination of SSGR + SPIR. Additional noise scans allowed pixelwise calculation of signal-to-noise ratio and contrast-to-noise ratio maps. Quantitative data at 7 T were compared with each other but not to 3 T. Two independent radiologists evaluated overall image quality, homogeneity and grade of fat suppression, and the delineation between 2 adjacent structures. Results were compared using Wilcoxon signed rank and paired sample t tests. Results: Relative signal-to-noise ratios of fat demonstrated that the SPIR technique reduced the fat signal to 45% ± 5.4%; SPAIR, 18% ± 1.2%; SSGR, 14% ± 1.1%; and SSGR + SPIR, 11% ± 0.3%. Contrast-to-noise ratio showed superior contrast between muscle-fat ( P < 0.001) and fluid-fat ( P ⩽ 0.001) for SSGR and SSGR + SPIR. The radiologists rated the overall image quality higher at 7 T than 3 T. The homogeneity and grade of fat suppression as well as the delineation between 2 different (adjacent) structures were rated best for SSGR + SPIR. Conclusions: At 7 T, fat saturation for clinical knee imaging using SSGR and the combination of SSGR + SPIR was superior compared with standard methods based on spectrally selective radiofrequency pulses.